Quantification of uPA in breast tumour tissue extracts by microarray immunoassay: Comparison with ELISA technology - Shi, Liu; Gehin, Thomas; Chevolot, Yann; Jacot, William; Lamy, Pierre-Jean; Laurenceau, Emmanuelle (Journal of Applied Biomedicine, 2018)
The urokinase-type plasminogen activator (uPA) and PA inhibitor 1 (PAI-1) play important roles in breast cancer metastasis through cell migration and invasion. They are clinically applicable prognostic and predictive markers. High levels of uPA and PAI-1 are associated with high risk of recurrence and adjuvant chemotherapy provides substantial benefit for this breast cancer population. The current sole validated method for quantifying uPA level in breast tumour tissue is ELISA assay. It requires 50–300 mg of fresh or frozen tissue, which is the main limitation for routine use. In this study, we evaluated the performances of customized antibody microarray to quantify uPA concentration from reduced extraction solution of breast tumour tissue and compared it with standard ELISA kit. We firstly optimized the elaboration of customized antibody microarray in order to sensitively detect and quantify uPA standard solutions. In the best conditions, we analysed uPA concentration in 16 cytosolic extracts from breast tumour tissue. Results showed that our customized antibody microarray could correctly quantify uPA concentration while consuming 100 times less volume of tumour tissue extraction solution than ELISA. Our antibody microarray is a powerful and promising tool for the miniaturization of the immunoassay quantification of uPA from breast tumour tissue extracts.
Keywords: nádory prsu; Prognosis; Breast Neoplasms; ELISA; metastázy nádorů; Neoplasm Metastasis; biologické markery; Humans; imunoanalýza; lidé; Biomarkers; Immunoassay; Urokinase-Type Plasminogen Activator; Tissue Array Analysis; aktivátor plazminogenu urokinázového typu; prognóza; čipová analýza tkání; Enzyme-Linked Immunosorbent Assay